Serving the servant : remembering Kurt Cobain - Goldberg, Danny, 1950- (Ecco, an imprint of HarperCollinsPublishers, 2019)
In early 1991, top music manager Danny Goldberg agreed to take on Nirvana, a critically acclaimed new band from the underground music scene in Seattle. He had no idea that the band<U+2019>s leader, Kurt Cobain, would become a pop-culture icon with a legacy arguably at the level of that of John Lennon, Michael Jackson, or Elvis Presley. Danny worked with Kurt from 1990 to 1994, the most impactful period of Kurt<U+2019>s life. This key time saw the stratospheric success of Nevermind, which turned Nirvana into the most successful rock band in the world and made punk and grunge household terms; Kurt<U+2019>s meeting and marriage to the brilliant but mercurial Courtney Love and their relationship that became a lightning rod for critics; the birth of their daughter, Frances Bean; and, finally, Kurt<U+2019>s public struggles with addiction, which ended in a devastating suicide that would alter the course of rock history. Throughout, Danny stood by Kurt<U+2019>s side as manager, and close friend.